Qualified Ingredients: Professionalism in Chefs’ Culinary Ingredient Selection - Faisal Akbar Zaenal; Hamka Naping; Syamsu Rijal; Yahya (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
Professionalism in gastronomy is often judged through visible outputs – brigade leadership, menu design, and guest experience – while chefs’ ingredient work remains largely backstage. Existing research has been less explicit about how chefs qualify ingredients as professional judgment under real-time service constraints. This study defines chefs’ knowledge of qualified ingredients and identifies two complementary evaluative logics: naturalistic quality in cookery and built-in quality in pastry and bakery. Drawing on a qualitative field study involving six purposively selected chefs working in hotel and independent operations, we conducted one-to-one, face-to-face interviews in 2024, transcribed them verbatim, and analysed the data thematically through manual coding. Chefs treated ingredient selection not as a routine purchasing task but as qualification work resolved through kitchen practice. Labels, brands, and price informed initial screening, while performance in use determined acceptance – sensory behaviour in context for cookery, and functional performance and repeatability within pastry-and-bakery production systems such as doughs, batters, creams, and fillings. The analysis also shows how these logics converge in hybrid judgement when service tightens margins, clarifying professionalism as the sustained labour of making ingredient decisions defensible so that technical integrity and intended sensory character can both hold under pressure. The study reframes ingredient selection as situated professional judgement and supports the inclusion of ingredient qualification as an explicit learning outcome in vocational culinary education.